Role of Foreign Banking Institutions in the European Union’s New Financial Markets - Dubauskas, Gediminas; Kowalski, Tadeusz; Vensel, Vello (Ekonomika, 2005)
The aim of this paper is to analyze the influence of foreign capital on the commercial banking sector of the emerging markets. The entry of foreign banks into the markets of Central and Eastern European countries (CEECs) has been rapid, remarkable and massive. This paper presents some empirical results of foreign banks’ entry, activities, operation and strategies in four CEECs (Estonia, Lithuania, Poland, and Romania); the first three of them have already joined the European Union integrated financial market in May 2004. The paper is based on a special survey results obtained by the authors from domestic and foreign-owned banks in these countries. Meanwhile mergers and acquisitions of the domestic banks are rather technical details of a foreign capital influx. According to our results, the main incentives motivating foreign entry have been to exploit new business opportunities and/or market expansion strategies. The host country market specifics, advantages and disadvantages of foreign banks, main target groups, and fields of activities, as well as foreign banks’ motives for strategic long-term stay in the host country market some more important characteristics of banks’ governance and management are also discussed. Interesting are the questions who are the key decision-makers in the majority of foreign-owned banks, how banks have adopted knowhow and risk management systems from the mother bank, how the mother bank helps its daughter in the host country, etc. The issues of the competitive pressure by foreign banks and the domestic banks’ survival prospects are also addressed in the paper.